Analisis Pelaksanaan Test, Lacak dan Isolasi (TLI) dengan Metode Case Study dalam Rangka Percepatan Pencegahan dan Pengendalian COVID-19 di Puskesmas se Kota Pekanbaru - Ikhtiyaruddin Ikhtiyaruddin; Nila Puspita Sari; Agus Alamsyah (LPPM Hang Tuah Pekanbaru, 2023)
Coronavirus disease 2019 (COVID-19) is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). SARS-CoV-2 is a new type of coronavirus that has never been found in humans before. Pekanbaru City in carrying out the COVID-19 response in accordance with the COVID-19 Handling Guidelines issued by the Indonesian Ministry of Health in 2020, the 5th revision, including implementing the 3T (Testing, Tracing, and Treatment) program. Based on the tracing number data on August 24, 2021, 1: 4.67, it means that for every 1 positive confirmed case, there are only 4 to 5 people whose close contacts are traced and tested. The purpose of this study is to know the results of the Analysis of the Implementation of Test, Trace, and Isolation (TLI) in the Context of Accelerating the Prevention and Control of COVID-19 at Public Health Centers in Pekanbaru City. This type of research is a quantitative and qualitative design with a case study approach. The sample selection of this research was purposive sampling, with a total sample of 20 which included 10 health centers in the city of Pekanbaru with informants including the doctor in charge and surveillance officers. Data collection was carried out by Focus Group Discussion with homogeneous informants with data analysis with content analysis. Testing has been carried out according to the guidelines for handling Covid-19 with close contact and symptoms. Tracing is still low, not in accordance with the provisions of the Ministry of Health and WHO 15, but still, an average of 3-4 people are being traced. Isolation in health services is low when compared to self-isolation at 5.2%. There is a need for integrated coordination between surveillance personnel and operators in an effort to reduce the number of Covid-19 cases and minimize the CFR/mortality rate.